Patterns of cancer care in Sri Lanka: Assessing care provision and unmet needs through an electronic database. (September 2020) - Wijeratne, Don Thiwanka; Gunasekera, Sanjeeva; Booth, Christopher M; Promod, Hasitha; Seneviratne, Sanjeewa
Highlights: Sri Lanka Cancer Registry collects basic data on all cancers in Sri Lanka. There is no systematic process to gather outcome data of any cancer in Sri Lanka. A low-cost, online database is established to capture comprehensive cancer data. This can potentially help health policy decision-making and improve cancer care. Abstract: Sri Lanka Cancer Registry (SLCR) maintained by the National Cancer Control Programme contains socio-demographic, histologic and some staging data on cancers. Currently there is no systematic process to gather outcome data of any cancer in Sri Lanka. The National Cancer Institute, Sri Lanka (NCISL) is the only dedicated cancer hospital in the country. This provides a unique opportunity to create an inception cohort that can be studied and followed up over an extended period. Our objective is to create an inception cohort of patients to study the patterns of cancer care at the NCISL. Detailed information on patient demographics, cancer diagnosis, treatment delivery, outcomes, comorbidities and health seeking behaviour are captured using an electronic database. This database was developed based on District Hospital Information System (DHIS 2) software platform. Approximately 4400 patients with breast cancer and 1200 patients with colorectal cancer have been collected both prospectively (February 1st 2018 to date) and retrospectively (January 1 st, 2016 to January 31 st, 2018) with ongoing prospective follow-up for all patients at 6-month intervals. Future of the data repository include coverage of cancers beyond breast and colorectal, expansion to include data from other public cancer treatment centres and linkage to the SLCR. This cancer care registry has the potential to form the cornerstone of cancer plans in Sri Lanka and to inform delivery of care and health policy decision-making enriching the SLCR. This registry is a crucial first step to build capacity in health systems research in Sri Lanka.